52 AUDIT CYCLE EXAMINING QUALITY IMPROVEMENT POST EMERGENCY DEPARTMENT MULTI-DISCIPLINARY SIMULATION BASED MEDICAL EDUCATION TRAINING ON HIP FRACTURE CARE. (18th November 2021) - Clancy, C; Mahony, R; Meighan, V
Abstract: Background: The care of patients with hip fractures is a surrogate marker of trauma care. Irish hip Fracture Standard 1 involves patients with a hip fracture being admitted to an orthopaedic ward bed within 4 hours of attending the ED. We wanted to audit our current practice and introduce a quality improvement project to improve the timeliness and efficiency of care of our hip fracture patients compared with the gold standard IHFS 1. We introduced a 90 minute multidisciplinary simulation training programme on the hip fracture pathway to our ED in February 2021. All key stakeholders were represented; from Emergency Medicine, Orthopaedics, Nursing (EM and Orthopaedic), Radiology, Radiography, Porters (32 people overall). Because of COVID-19, the training was available in person and online via Zoom. Methods: We performed a retrospective audit of patients presenting to TUH ED with a proximal third of femur fracture between 4 th February and 31 st March inclusive in 2020 and 2021, pre and post introduction of multidisciplinary simulation based medical education on the hip fracture pathway. Data was collected from the electronic record database (Symphony). We recorded the following data; Results: 2020 n = 31. Average time to ward—8 hrs 29 mins. 26% patients reached ward <4 hours. (8/31). 2021 n = 25. Average time to ward—5 hrs 58 mins (32% reduction vs 2020). 72% patients reached ward <4 hours. (18/25) (46% increase vs 2020). Conclusion: Simulation based medical education is a successful intervention to improve compliance with our hip fracture pathway, time from presentation to transfer to an orthopaedic ward bed and achieve IHFS 1.